Ejercicios literarios intermediales en la escritura fílmica de Carlos Araya Díaz: espacios comunes y sujetos menores en Población flotante - Nibaldo Acero; Javier Pérez (Cuadernos LIRICO)
Our objective is to study the novel Población Flotante (2019), by the filmmaker-writer Carlos Araya Díaz, from the intermediate theory and the remediations that he develops from the cinematographic language to the narrative, having as comparative material the documentary Viaje espacial (2019). The hypothesis we present is that Araya Díaz, subscribes his work as a filmmaker in literature with the aim of going into the common spaces and minor subjects that he films-narrative, with a cinematographic language (shots and editing) to address a range of contemporary social problems, such as migratory, gender, classism, among others.